LANDSLIDE FIELD MAPPING: IFFI-RESTART FORMS FOR DATA ACQUISITION AND MANAGEMENT - DE DONATIS, Mauro; F. PAPPAFICO, Giulio; BONÌ, Roberta; FRANCIONI, Mirko; MARINO, Lucia; MORELLI, Stefano; VYZHVA, Sergii; ZATSERKOVNY, Vitalii (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Over the last few decades, the approach to geological and geomorphological surveys has changed remarkably. The advent of digital tools has allowed significant advances in the acquisition and management of survey data. In this paper, we demonstrate the development and testing of a new and effective digital survey method that allows for the fast acquisition and collaborative storage and management of data and information. This method was tested in collaboration with five universities for the mapping and classification of landslides in 249 survey areas in Central Italy and, more precisely, in the municipalities affected by the 2016 Central Italy Earthquake. Geological and geomorphological surveys were carried out in the field with tablet PCs, GPS, and cameras. The survey project for collecting field data was based on the structure of the Italian Landslide Inventory (IFFI) and the Territorial Resilience Central Apennines Earthquake Reconstruction (ReSTART) projects. The structure of the database and input forms were implemented for these aims. Moreover, the data and information were retrieved and organised in detailed records useful to the administrative entities.